The Critical Role Of Nurse Competence And Communication In Enhancing The Quality Of Care During Electroconvulsive Therapy (ECT): A Literature Review - Priasmoro, Dian Pitaloka; Lestari, Retno (Pusat Penelitian dan Pengabdian Masyarakat STIKES Banyuwangi, 2025)
Electroconvulsive Therapy (ECT) remains one of the most effective interventions for severe psychiatric disorders. However, despite its established clinical efficacy, ECT continues to be associated with stigma, fear, and misinformation, which significantly impacts patient satisfaction and adherence. Nursing care plays a critical role in shaping patients' perceptions and overall satisfaction with ECT. This literature review explores the influence of nursing education on patient satisfaction throughout the ECT process, highlighting how well-trained nurses contribute to improved communication, reduced anxiety, and enhanced patient-centered care. A systematic literature search was conducted using databases such as EBSCO, ScienceDirect, ResearchGate, IEEE Access, and DOAJ, applying the PRISMA framework to identify, select, and analyze relevant studies. Articles published in English from 2019 to 2025. Findings demonstrate that structured nursing education programs focusing on procedural knowledge, therapeutic communication, and stigma reduction significantly enhance patient satisfaction across pre-treatment, intra-treatment, and post-treatment stages. Educated nurses are better equipped to deliver accurate information, address concerns, and foster trust, ultimately improving the overall patient experience. This review underscores the importance of integrating ECT-specific content into nursing curricula and ongoing professional development to ensure that psychiatric nursing practice aligns with evidence-based, patient-centered care principles.